2019
DOI: 10.1108/ijilt-11-2018-0129
|View full text |Cite
|
Sign up to set email alerts
|

Digital creativity: learning by story driven digital production

Abstract: Purpose The goal to stimulate perspective taking and inference making on social phenomena, such as gender roles in society, has proven to be difficult to achieve in general and in particular for primary school students. Thus, the purpose of this paper is to develop creative models and concepts for learning that provide guidance addressing these challenges. Design/methodology/approach A case study methodology, including classroom observations, teacher interviews and analysis of videos created by students, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
1
1
0
1
Order By: Relevance
“…The research reported similar products to what was observed, which include digital stories (Girmen et al, 2019;Kimbell-Lopez et al, 2016), information projects (Koh, 2013;Koh et al, 2019), graphic design (Hsu et al, 2016), 3D modelling (Yildirim, 2018), music (Kim, 2013), and blogging (Alhinty, 2014;Freeman et al, 2016). There were other products reported that were not observed in my study, such as coding and creating digital games (Akcaoglu & Green, 2018;Ejsing-Duun & Skovbjerg, 2016;Liao et al, 2016;Melander Bowden, 2019), non-digital products using 3D printers (Hansen et al, 2019), animated digital stories (Liao et al, 2016;Yildiz Durak, 2018), and digital media (videos) (Spante, 2019). The systematised review conducted in my research shows that most of the students' products studied were part of an intervention.…”
Section: Production Mediumsupporting
confidence: 70%
“…The research reported similar products to what was observed, which include digital stories (Girmen et al, 2019;Kimbell-Lopez et al, 2016), information projects (Koh, 2013;Koh et al, 2019), graphic design (Hsu et al, 2016), 3D modelling (Yildirim, 2018), music (Kim, 2013), and blogging (Alhinty, 2014;Freeman et al, 2016). There were other products reported that were not observed in my study, such as coding and creating digital games (Akcaoglu & Green, 2018;Ejsing-Duun & Skovbjerg, 2016;Liao et al, 2016;Melander Bowden, 2019), non-digital products using 3D printers (Hansen et al, 2019), animated digital stories (Liao et al, 2016;Yildiz Durak, 2018), and digital media (videos) (Spante, 2019). The systematised review conducted in my research shows that most of the students' products studied were part of an intervention.…”
Section: Production Mediumsupporting
confidence: 70%
“…Dalam pelaksanaannya, membiasakan keterampilan hidup di rumah tidaklah semudah yang dibayangkan. Faktor kurangnya semangat anak dan keterbatasan kemampuan orang tua dalam mendampingi anak menjadi tantangan dalam penerapan belajar di rumah (Malta Campos & Vieira, 2021;Neitzel et al, 2019;Spante, 2019). Berdasarkan observasi pada beberapa Lembaga Pendidikan Anak Usia Dini menyatakan bahwa sebagian besar orang tua tidak telaten dan sering mengeluhkan kondisi anaknya saat belajar.…”
Section: Pendahuluanunclassified
“…Destacan las diferencias encontradas en cuanto a la concepción y usos que se le atribuyen a las tecnologías dentro del proyecto educativo general y en particular reflejan el debate existente en la sociedad sobre la naturaleza y los contenidos de la CD (Pötzsch, 2016). En algunos casos, focalizan los procesos de innovación en relación al uso de la tecnología, frente a otros centros donde la innovación se vincula a metodologías (Spante, 2019) o incluso a contenidos y objetivos relacionados con el pensamiento computacional.…”
Section: Valoración De La Inclusión Del Alumnado Con Necesidades Espeunclassified